Point mass balance (floating date) Weißseespitze (Tyrol, Austria) 2017 et seq - Martin Stocker-Waldhuber; Lea Hartl; Bernd Seiser; Giulia Bertolotti; Andreas Gschwentner; Andrea Fischer (PANGAEA, 2025)
Seven ablation stakes were installed near the summit of Weißseespitze (Tyrol, Austria) between 2017 and 2019 to measure ice ablation in the highest region of Gepatschferner. An additional stake was added in 2022. The stakes are positioned at elevations between 3488 and 3506 m a.s.l.. The period of record varies between different stakes. Stake readings were carried out in irregular intervals approximately two to four times per year. Observations include snow depth at the stake locations (if any) and changes of the ice surface relative to the stake. The latter is typically a negative value referring to a decrease in surface elevation due to ice ablation. In some cases, the formation of superimposed ice caused slightly positive surface change. An ice density of 900 kg/m3 was assumed to convert ice ablation into mass change in water equivalent units. Snow density was not measured. Stake positions were recorded with a GNSS receiver (Topcon HIPER V) data unit during most readings and corrected by post-processing. If no position is stated for a given reading, the position was not recorded and the position of the previous or subsequent reading (whichever is closer in time) should be assumed.